Benchmarking the nutrient composition and labelling practices of finger foods and snacks for older infants and young children across seven Southeast Asian countries - Alissa M. Pries; Eleonora Bassetti; Jessica M. White; Anzélle Mulder; Diane Threapleton; Jessica Blankenship (Wiley, 2023)
Abstract Ensuring consumption of nutrient‐dense, safe and appropriate complementary foods among older infants and young children (IYC) 6-36 months of age is critical for enabling optimal growth and development. The ubiquitous availability of and high demand for commercially packaged snack foods has culminated in a growing trend of snack food products specifically produced and promoted for older IYC. Commercially produced complementary foods (CPCF) that are finger foods/snacks often contain added sugars, excessive sodium content and high total sugar content, making them inappropriate for this young population. This study benchmarked the nutrient composition and labelling practices of CPCF finger foods/snacks available for purchase in seven countries in Southeast Asia. The study adapted a nutrient profiling model from the WHO Regional Office for Europe to determine the proportion of products suitable for promotion for older IYC. Of the total 606 products identified, 8.2% were automatically categorized as not suitable because they were confectionery items. Of the remaining 556 products assessed, over 85% failed to meet all nutrient composition requirements, with the presence of added sugars/sweeteners and excessive sodium and total sugar contents the primary reasons for failure. Products also demonstrated concerning labelling practices, with all of the products (98.6%) displaying an inappropriate claim on the label. These findings reveal major concerns with the nutrient composition and labelling practices of CPCF finger foods/snacks in the SEA region and should serve as an alarm bell for regulatory action. National binding legal measures, such as mandatory standards for composition and labelling are urgently needed.